Immobilization of TiO2 Semiconductor Nanoparticles onto Posidonia Oceanica Fibers for Photocatalytic Phenol Degradation - Latifa Morjène (MDPI AG, 2021)
A new composite photocatalyst called POF/TiO2 was prepared from commercial P25 TiO2 and Posidonia oceanica fibers (POF), a biomaterial collected from Tunisia’s beach. The composite material was prepared by a classical sol-gel synthesis and was characterized by different methods. SEM images show a TiO2 layer formed on top of the fibers, which was verified by XRD and XPS. Diffuse reflectance UV-vis spectroscopy shows that the layer has the same optical properties (Eg = 3.0 eV) as bulk P25. The photodegradation of phenol as a model compound was studied under different operating conditions using POF/TiO2 and the results show degradation efficiencies between 4% (100 ppm) and 100% (<25 ppm) after 4 h of UV-C light irradiation (254 nm) using a POF/TiO2 concentration of about 1 g/L. The composite material showed good stability and could be recycled up to three times.